Objective outcome measures may demonstrate continued change in functional recovery in patients with ceiling effects of subjective patient-reported outcome measures after surgery for lumbar degenerative disorders - Ziga, Michal; Sosnova, Marketa; Zeitlberger, Anna M; Regli, Luca; Bozinov, Oliver; Weyerbrock, Astrid; Ratliff, John K; Stienen, Martin N; Maldaner, Nicolai (The spine journal, 2023)
BACKGROUND CONTEXT: The 6-minute walking test (6WT) has been previously shown to be a reliable and valid outcome measure. It is unclear if the 6WT may further help to detect differences in well performing patients that reach a ceiling effect in PROMs after surgery. PURPOSE: To evaluate changes and timing of change in objective functional impairment (OFI) as measured with the smartphone-based 6WT in relation to patient-reported outcome measures (PROMs) after surgery for degenerative lumbar disorders (DLD). STUDY DESIGN: Prospective observational cohort study. PATIENT SAMPLE: Fifty consecutive patients undergoing surgery for DLD. OUTCOME MEASURES: Patients self-determined their OFI using the 6WT application (6WT-app) and completed a set of paper-based PROMs before, 6 weeks and 3 months after surgery. METHODS: Fifty patients undergoing surgery for DLD were assessed preoperatively (baseline), 6 weeks (6W) and 3 months (3M) postoperatively. Paired sample t-tests were used to establish significant changes in raw 6-minute walking distance (6WD) and standardized Z-scores, as well as PROMs. Pearson correlation coefficient was used to define the relationship between 6WT and PROMs. Floor and ceiling effects were assessed for each PROM (visual analogue scale [VAS], core outcome measure index [COMI], Zurich claudication questionnaire [ZCQ]). RESULTS: Mean 6WT results improved from 377 m (standard deviation - SD 137; Z-score: 1.8, SD 1.8) to 490 m (SD 126; -0.7, SD 1.5) and 518 m (SD 112; -0.4, SD 1.41; all p<.05) at 6W and 3M follow-up. No significant improvement was observed between 6W and 3M for the ZCQ, VAS back and leg pain. While correlation between 6WT and all PROMs were weak at baseline, correlation coefficient increased to moderate at 3M. A considerable ceiling effect (best possible score) was observed, most notably for the ZCQ physical performance, VAS back and leg pain in 24%, 20%, and 16% of patient at 6W and in 30%, 24%, and 28% at 3M. CONCLUSIONS: Objective functional tests can describe the continued change in the physical recovery of a patient and may help to detect differences in well performing groups as well as in cases where patients' PROM results cannot further improve because of a ceiling effect.
Keywords: Prospective Studies; Objective functional impairment; hodnocení výsledků zdravotní péče; Humans; prospektivní studie; Lumbar Vertebrae; Intervertebral Disc Degeneration; 6-Minute walking test; 6WT; Responsiveness; výsledek terapie; Functional self-assessment; Treatment Outcome; Patient Reported Outcome Measures; hodnocení výsledků péče pacientem; bolest; lidé; degenerace meziobratlové ploténky; bederní obratle; Outcome Assessment, Health Care; Pain